Working alliance and its link to guidance in an internet-based intervention for depressive disorders: a secondary analysis of a randomized controlled trial - Haaf, Raoul; Schefft, Cora; Krämer, Rico; Klein, Jan Philipp; Köhler, Stephan (Frontiers in Psychiatry, 2024)
Background: Guided Internet-based interventions (IBIs) are typically found to be more effective than unguided ones, but the reasons behind this are not well understood. The therapist-client working alliance, crucial in face-to-face psychotherapy, is also increasingly recognized as an important factor in IBIs. This study examines trajectories of the working alliance and its relationship to therapeutic guidance through a secondary analysis of a randomized controlled trial (RCT) on Selfapy, a 12-week IBI based on cognitive behavioral therapy for depressive disorders. The trial compared a therapistguided version (with weekly calls) to an unguided version (n = 301, mean age 37 years, 83% female, mean BDI-II = 30.09). Methods: Based on an intention-to-treat approach, this study investigates within-and between-group differences in the quality of the working alliance, assessed with the WAI-SR questionnaire at mid-and post-treatment via repeated measures ANOVA. Furthermore, correlations and mediation analyses were conducted to explore the relationship between the working alliance and outcomes, as well as adherence parameters. Results: Findings indicate that the IBI was successful in fostering a robust working alliance in both intervention groups, with similar ratings at mid-treatment but significantly higher ratings in the guided group at post-treatment (Cohen's d = -0.38). Post-treatment working alliance scores were positively linked to symptom reduction at posttreatment (guided: r = 0.25, unguided r = 0.15) and follow-up (guided: r = 0.25, unguided: r = 0.17). In the unguided group, the association was primarily driven by the subscale task. Serial mediation analysis indicated that the relationship between guidance and outcomes at follow-up was mediated by working alliance (b = 0.59; 95% CI: 0.14, 1.22) and a link between working alliance and adherence (b = 0.15; 95% CI: 0.04, 0.34). Conclusions: Considering limitations like using a questionnaire developed for face-to-face therapy, findings support the importance of the working alliance in guided IBIs, while also providing new insights into its role and formation in unguided IBIs. The potential benefits of a strong working alliance, notably by improving adherence, may prove crucial for integrating guided as well as unguided IBIs into routine use, indicating the need for additional research in this context.